A proposed training program to develop graphic design skills among tenth grade students in Jordanian Ministry of Education schools and their attitudes towards it - Baker Abel Aziz Dabaibeh; Ibrahim Al-baher (Technium Social Sciences Journal, 2024)
The current study aimed to propose an training program and measure its impact on developing graphic design skills among tenth grade students in the Jordanian Ministry of Education schools and their attitudes towards it. The study population consisted of all tenth-grade students at Khadija Bint Khuwaylid Secondary School for Governmental Girls in the Directorate of Education for the Rusaifa region during the first semester of the academic year (2023-2024), as they numbered (50) students. The semi-experimental approach was used in the current study with two groups. experimental and control. To achieve the objectives of the study, one questionnaire and two tests were developed, and its validity and reliability were confirmed. The study concluded that the effect of the training program on acquiring graphic design skills among tenth grade students was high. In addition to the existence of apparent differences between the mean scores of the experimental and control groups in the post-measurement in the graphic design skills test in favor of the experimental group. And that there are statistically significant differences at the significance level (α ≤ 0.05) between the means of the experimental and control groups in the graphic design skills test. The study also found that the attitudes of tenth grade students towards the training program were high. The study recommended that the Ministry of Education in its various directorates adopt the proposed training program to measure graphic design skills. By perusing it and trying to apply it in its various schools, and for academic leaders to assume graphic design skills critical importance Where it works to stimulate the conduct of studies and research from time to time, to find out the reality of those skills, and work seriously to develop and update them to take into account the technical development of the number of e-training programs.